Combining Telbivudine with Tenofovir in hepatitis B virus related acute on chronic liver failure reduce the risk of renal impairment. - Manik, Abul Hayat; Malakar, Debraj; Resma, Tania Islam; Ananya, Kaniz Fatema; Mamun, Shameem Al; Rahman, Salimur (Bangladesh Critical Care Journal, 2022)
Introduction: Chronic hepatitis B virus (HBV) infection is a major health problem because of its worldwide distribution and its potential adverse sequel, including acute-on-chronic liver failure (ACLF), liver cirrhosis and hepatocellular carcinoma. Short term prognosis of patients with spontaneous severe acute exacerbation of CHB leading to ACLF- like presentation is extremely poor, with mortality ranging from 30% to 70%. Therefore, early and rapid reduction of HBV DNA is the essence of therapy in ACLF-B. Methods: Patients with spontaneous reactivation of HBV [(ALT >5 × upper limit of normal or >2 × baseline) and HBV DNA >20,000 IU/ml] were randomized to Tenofovir mono therapy (300 mg/day) or Tenofovir plus Telbivudine (600 mg/day) dual therapy along with standard medical treatment. Clinical and biochemical parameters were evaluated at baseline, 1 week, 4 weeks and at 3 months. Virological evaluation was done at baseline and at 3 months. Primary end point was reduction of HBV DNA. Secondary end point was reduction of liver related complication, therapy related adverse effects and survival at 3 months. Results: 27 patients were enrolled and 15 of them received mono therapy with Tenofovir and 12 patients received dual therapy (Tenofovir plus Telbivudine). Baseline parameters in two groups had no significant difference. Both groups significantly improve s. bilirubin, ALT, INR, CTP score and MELD score. Only MELD score showed significant improvement in patient with dual therapy at 3 months in comparison of mono therapy. 11 patient on Tenofovir mono therapy (n=15) showed undetected HBV DNA (91.7%) at 3 month and one patient had detectable HBV DNA (<2,000 IU/ml). 10 patients on dual therapy (n=12) had undetectable HBV DNA (100%). Patients receiving dual therapy showed significant improvement in AKI on follow up compared to those on Tenofovir mono therapy. Among 5 deaths, 3 had received mono therapy with Tenofovir and 2 had received dual therapy. Predictors of mortality were high S. bilirubin (25.8±7.8), HBV DNA (5.18±1.17 log10 IU/ml), MELD score (33.0±4.2) and CTP score (12.2±0.8). Conclusion: In spontaneous reactivation of hepatitis B presenting as acute on chronic liver failure, combination of Telbivudine plus Tenofovir is potentially safer with less risk of Tenofovir related nephrotoxicity and hence improved outcomes. Bangladesh Crit Care J March 2022; 10 (1): 48-51